P35 Elevated tricuspid regurgitation jet velocity on echocardiogram in Sickle Cell Disease is associated with raised inflammatory mediators and low steady state haemoglobin but not other markers of haemolysis. (16th November 2010) - Ranu, H; Connell, E; Hunt, C; Boa, F; Lee, J; Brown, L; Willis, F; Buyck, H; Madden, BP
Abstract : Introduction and Objectives: Pulmonary hypertension (PH) in Sickle cell disease (SCD) is defined as tricuspid regurgitation jet velocity ≥2.5 m/s on trans thoracic echocardiogram. It is an important complication of SCD and is associated with significant mortality. Haemolysis with impairment of the nitric oxide pathway is felt to play a major part in its pathogenesis. We have examined the association of haemolytic markers and inflammatory cytokines in haemoglobin SS (HbSS) adults with PH (TRV≥ 2.5 m/s) and without PH (TRV <2.5 m/s). Cytokines studied included interleukin 8 (IL-8), which may have a role in promoting adhesion of sickled red cells to vascular endothelium and stem cell factor (SCF), which acts on erythroid progenitor cells. Methods: 32 adult HbSS patients (mean age 37 years ± 11.6, median 37 years) were recruited at steady state defined as 2 weeks or more following an acute crisis. Serum levels of haemolytic markers (haemoglobin, lactate dehydrogenase LDH, bilirubin), asymmetric dimethylarginine (ADMA a naturally occurring nitric oxide synthase inhibitor), SCF and IL 8 were measured. Results: Results are given in Abstract P35 Table 1 and expressed as mean ± SD. TRV was significantly correlated with Hb (p=0.003 r= − 0.51), ADMA (p< 0.05, r= 0.35), IL 8 (p= 0.009, r= 0.48) and SCF (p=0.006, r= 0.51). Conclusion: PH in SCD is associated with lower haemoglobin and ADMA but not other markers of haemolysis. There is a significant association of TRV with IL 8 and SCF, which has not been previously described in adults. Inflammatory mediated endothelial dysfunction is likely to also play an important role in the pathogenesis of PH associated with SCD. The roles of IL 8 and SCF warrant further investigation.